Guide for creating accessible digital content: Documents, presentations, videos, audios, and web pages (Universidad de Alcalá. Servicio de Publicaciones, 2015)
erefore, in addition to providing guidance, examples of how to perform them using some of the most used editors of digital content are presented. Among others, Microsoft Office suite to create documents (with Word) and slide presentations (with PowerPoint) are used, because they offer advanced mechanisms that help the author to create and revise the accessibility of content.